The Biorevitalization Effect of Serum Containing Rose Apple Leaf Extract on the Parameters of Premature Skin Aging - Cynthia, Gabriella; Fachrial, Edy; Ehrich Lister, I. Nyoman (British Journal of Healthcare and Medical Research, 2022)
Rose apple (Syzygium jambos) is known for its antioxidants and could potentially be used as an anti-aging cosmetic. This study reported the potential of rose apple leaf extract as a skin serum for the biorevitalization- with improvement based on pigmentation, wrinkles, pore, and sensitivity parameters in the skin of women aged 30 to 40. The skin serum was formulated with various concentrations of 5%, 10%, and 15% of rose apple leaf extract. The Pretest-Posttest with Control Group Design were conducted by measuring skin condition with the API-100 Aram Huvis Innovation Skin Analysis System. Data analyses using the Kruskal-Wallis’s test and Mann-Whitney’s test. The phytochemical contents of rose apple leaf extracts showed alkaloids, flavonoids, saponins, phenol as gallic acid, and tannic acid, which function as antioxidants that is comparable to vitamin C with IC50 of up to 7.29%. Experimental data showed that rose apple leaf extract affects skin biorevitalization based on reduction in pore size, skin pigmentation, and sensitivity parameters. This study strongly suggests the potential of rose apple leaf extract as an anti-aging ingredient to prevent premature skin aging.